Eed-dependent histone modification orchestrates the iNKT cell developmental program alleviating liver injury - Guo, Yun; Ohki, Shun; Kawano, Yohei; Kong, Weng Sheng; Ohno, Yoshinori; Honda, Hiroaki; Kanno, Masamoto; Yasuda, Tomoharu (Frontiers in Immunology, 2024)
Polycomb repressive complex 2 (PRC2) is an evolutionarily conserved epigenetic modifier responsible for tri-methylation of lysine 27 on histone H3 (H3K27me3). Previous studies have linked PRC2 to invariant natural killer T (iNKT) cell development, but its physiological and precise role remained unclear. To address this, we conditionally deleted Eed, a core subunit of PRC2, in mouse T cells. The results showed that Eed-deficient mice exhibited a severe reduction in iNKT cell numbers, particularly NKT1 and NKT17 cells, while conventional T cells and NKT2 cells remained intact. Deletion of Eed disrupted iNKT cell differentiation, leading to increased cell death, which was accompanied by a severe reduction in H3K27me3 levels and abnormal expression of Zbtb16, Cdkn2a, and Cdkn1a. Interestingly, Eed-deficient mice were highly susceptible to acetaminophen-induced liver injury and inflammation in an iNKT cell-dependent manner, highlighting the critical role of Eed-mediated H3K27me3 marks in liver-resident iNKT cells. These findings provide further insight into the epigenetic orchestration of iNKT cell-specific transcriptional programs.